Numerical investigation on mechanisms and performance of column attachment ventilation for winter heating. (September 2021) - Yin, Haiguo; Huo, Yaokun; Wang, Yuanyuan; Ji, Daina; Wang, Jiali; Ma, Zhenjun; Li, Angui
Abstract: Column attached ventilation (CAV) is a new form of air distribution based on pillars widely distributed in buildings. Due to thermal buoyancy in the room, the airflow mechanism and performance of CAV is uncertain when it is applied for winter heating, especially in buildings with large space. In this study, a simplified three-dimensional model was established based on a shopping mall. A Computational Fluid Dynamics (CFD) method was employed to simulate the airflow in the room. Archimedes number (Ar) was used to study air distribution and ventilation performance. Results indicated that CAV could be used for room heating, and inertia force was the main driving force of the airflow. In the occupied zone, air velocity and temperature could be controlled by supply air velocity and temperature. Ar was related to air distribution and ventilation effect. In selected cases, Ar less than 2.241 × 10 −3 was the prerequisite for effective air distribution. Heat removal effectiveness was linearly related to Ar, and it increased by about 0.01 when Ar reduced by 0.1. CAV saved more energy than mixing ventilation to achieve the same parameters of the occupied zone. These results provide a theoretical basis for the application of CAV in winter conditions. Highlights: Column attached ventilation (CAV) can be used for room heating. Archimedes number can determine whether CAV forms effective air distribution. In the occupied zone, the inertial force dominates the CAV air distribution. Average room temperature increases linearly with increasing supply air temperature. CAV has a higher heat and CO2 removal effectiveness than mixing ventilation.